Deeply responsible business a global history of values-driven leadership - Jones, Geoffrey; ProQuest (Firm) (Cambridge : Harvard University Press, 2023)
Deeply Responsible Business profiles corporate leaders of the past two centuries who made social missions vital to their businesses. Geoffrey Jones explores the characters and motivations of fourteen such leaders and compares their deep social and environmental commitments to the lukewarm "corporate social responsibility" of today.
Off-Campus Access: Athens ID and Password Required
On-Campus Access: No User ID or Password Required
Access type: Perpetual access for unlimited users
Includes bibliographical references and index.
GenEd
Mode of access: Internet
Keywords: Social responsibility of business -- History -- Case studies; Business ethics -- History -- Case studies; Leadership -- Moral and ethical aspects -- History -- Case studies; Organizational change -- History -- Case studies; Electronic books